Kontribusi Wanita Tani Pada Usaha Tani Cabai Rawit - , Novi Nurhayati; Risca Permatasari; Dwi Tri Nilasari (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2024)
The cayenne pepper plant commodity is a strategic agricultural commodity, has high economic value and a wide market share. The cultivation of cayenne pepper plants in West Kotawaringin Regency is generally carried out by farming households. A farming household is a group of people who live in part or all of a building and generally eat together from one kitchen with the head of the household working in the agricultural sector. The formulation of the problem in this research is whether the workforce in cayenne pepper farming is experiencing a shift to female farming workforce. In answering the research objective